Rickets and tracheobronchomalacia - Bangalore, Harish (BMJ Publishing Group, 2009)
Rickets is increasingly encountered in practice, even in the Western world. One recent publication reports an overall incidence of 7.5 per 100 000 children. Respiratory infections are well known to be associated with rickets. We present a case of rickets with severe respiratory complications. Tracheobronchomalacia was detected on bronchoscopy. We believe that tracheobronchomalacia may be a hitherto unrecognised finding in rickets and may need to be investigated further.